2016
DOI: 10.1002/btpr.2300
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the effect of multiple Fc glycan attributes on the effector functions and FcγRIIIa receptor binding activity of an IgG1 antibody

Abstract: N-linked Fc glycosylation of IgG1 monoclonal antibody therapeutics can directly influence their mechanism of action by impacting IgG effector functions such as antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). Therefore, identification and detailed characterization of Fc glycan critical quality attributes (CQAs) provides important information for process design and control. A two-step approach was used to identify and characterize the Fc glycan CQAs for an IgG1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…A broad body of literature shows that different glycoforms can mediate cellular effector functions, like ADCC 3-6 (reviewed in refs. 1,7, and 8), and CDC 3,6,35 (reviewed in refs. 10,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A broad body of literature shows that different glycoforms can mediate cellular effector functions, like ADCC 3-6 (reviewed in refs. 1,7, and 8), and CDC 3,6,35 (reviewed in refs. 10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The presence or absence of fucose on the first core GlucNAc dramatically impacts antibody-dependent cell-mediated cytotoxicity (ADCC). 1,[3][4][5][6][7][8] Similarly, the level of terminal galactosylation affects complement-dependent cytotoxicity (CDC). 3,6,[9][10][11] Antibodies with high mannose-containing glycosylation structures (Man5 and higher) are cleared from the bloodstream at a faster rate than those with mature, complex type oligosaccharides, which has direct implications for drug efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, whether the bisecting GlcNAc directly affects IgG functionality has still not been adequately addressed. The function of the rest of the glycan features is less clear14163233, although a recent study indicates an additional role of galactose for FcγRIIIa binding343536.…”
mentioning
confidence: 99%
“…The impact of removal of galactose is highly dependent on the IgG subclass, receptor class, and the specific cell types or other factors used for the assays . There are several studies indicating that removal of terminal galactose has no impact on Fcγ receptor bindings or ADCC . Also, several studies have demonstrated that removal of terminal galactose results in a slight decrease in antibody binding to Fcγ receptors .…”
Section: Impact Of Various Oligosaccharides On Structure Stability Amentioning
confidence: 99%